Ratio of maximum to minimum tumor diameter can predict the pathology type of renal cell carcinoma before surgery. Issue 1 (February 2021) - Jiang, Weixing; Wang, Dong; Shi, Hongzhe; Shang, Bingqing; Wen, Li; Zhang, Lianyu; Zhang, Jin; Zhang, Huijuan; Zheng, Shan; Shou, Jianzhong
Introduction: Previous reports have described several methods and markers used to distinguish pathologic subtypes of renal cell carcinoma (RCC). This study aimed to evaluate the utility of the ratio of maximum to minimum tumor diameter (ROD) in predicting pathologic subtypes of RCC. Methods: Data from patients with RCC who underwent surgery between January 2015 and December 2019 were reviewed retrospectively. The cutoff value for ROD was calculated using receiver operating characteristic (ROC) curve analysis. Results: In the clear cell RCC (ccRCC) and non-ccRCC groups, the optimal ROD cutoff value to predict ccRCC was determined to be 1.201 (sensitivity, 90.7%; specificity, 76.1%; area under the ROC curve [AUC], 0.827; p < 0.001). In the non-ccRCC group, the cutoff value for ROD in predicting papillary RCC was 1.092 (sensitivity, 87.9%; specificity, 40.5%; AUC, 0.637; p = 0.003). Compared with patients with ROD <1.201, more patients in the ccRCC group exhibited tumors with an ROD ⩾1.201 (14.2% versus 85.8%, respectively; p < 0.001). Multivariate analysis of preoperative features revealed that ROD ⩾1.201 was an independent predictive factor for ccRCC. In addition, patients with ROD ⩾1.201 had higher percentages of Fuhrman grade III/IV (91.2% versus 8.8%; p = 0.014), tumor necrosis (86.7% versus 13.3%; p = 0.012) and sarcomatoid differentiation (90.6% versus 9.4%; p < 0.001). Conclusions: ROD was a novel indicator for preoperatively predicting histologic type in patients with RCC. ROD cutoff values of 1.201 and 1.092 were the most discriminative for ccRCC and papillary RCC, respectively. Moreover, ROD ⩾1.201 was associated with high Fuhrman grade, sarcomatoid features, and tumor necrosis.